The Analysis of Factors that Influence Stunting - Santoso, Puguh; Pujianto, Tutut (Journal of Ners and Midwifery, 2024)
Stunting in children is a national problem caused by many factors that harm human resources in the future, including an impact on decreasing intelligence, vulnerability to disease, hampering economic growth, work productivity, exacerbating inequality, and height growth is shorter than age in general. Stunting in children under five is a consequence of several factors that are often associated with poverty, including nutrition, health, sanitation, and the environment There are five main factors that cause stunting, namely poverty, social and cultural, increased exposure to infectious diseases, food insecurity and community access to health service. The purpose of this literature review was to analyze the factors that influence stunting. The article was obtained from a SINTA accredited journal published in the 2013-2023 period with the same title, as well as the same research design. The selected articles were then tested for plagiarism, and nine articles with the smallest plagiarism level were selected. Analysis PICO (Population, Intervention, Comparison, Outcome) is carried out on each article, followed by making conclusions. The results of the analysis determined that factors that influence stunting include social and cultural, increased exposure to infectious diseases, food insecurity and community access to health services alone or together. The author hopes that this research will further greatly help how to do health promotion, case finding and prevention, and, many sectors must be involved and work together for the problem of stunting.